Muslim Zion: Pakistan as a political idea - "Devji, Faisal" (Boston, 2013)
Devji offers a detailed analysis of the various political and ideological forces that were at play in the buildup to Pakistan's creation. Devji's larger project seems to be to mitigate the tendency to look at historical phenomena from the 20th and 21st centuries isolated from their global context...He notes that Jinnah 'seems to have possessed more books on the problems of European Jewry than on any Muslim people or country.' Devji also believes that the formation of Pakistan set a precedent that made Israel possible.
Keywords: Islam and politics